Tongluo Yishen Decoction Ameliorates Renal Fibrosis via Regulating Mitochondrial Dysfunction Induced by Oxidative Stress in Unilateral Ureteral Obstruction Rats - Jia, Qi; Han, Lin; Zhang, Xiaoyu; Yang, Wenning; Gao, Yushan; Shen, Yifan; Li, Bing; Wang, Shuyan; Qin, Mingzhen; Lowe, Scott; Qin, Jianguo; Hao, Gaimei (Frontiers in Pharmacology, 2021)
Tongluoyishen (TLYS) decoction is an herb that is extensively applied for the treatment of chronic kidney disease (CKD) in traditional Chinese medicine. In this study, 37 different dominant chemical constituents of TLYS were identified. Rats with unilateral ureteral obstruction (UUO) were used as animal models, and TLYS decoction was administered orally for 14 days. TLYS decoction reduced the levels of renal function indicators, serum creatinine levels and blood urea nitrogen levels and alleviated renal pathological changes. Gene Ontology (GO) and KEGG pathway analyses of RNA sequencing data showed that TLYS decoction had significant effects on biological processes, cellular components and molecular functions in UUO rats and that the phagosome (a membrane source in the early stages of autophagy), lysosome (an important component of autolysosome), and oxidation pathways (which contribute to mitochondrial function) might be related to the antifibrotic effects of TLYS decoction. Moreover, we found significant mitochondrial function impairment, including a decreased mitochondrial membrane potential (MMP) and an imbalance in mitochondrial dynamics, excessive oxidative stress, and activation of Pink1/Parkin-mediated mitophagy in UUO rats. Treatment with TLYS decoction significantly increased the MMP, normalized mitochondrial dynamics and ameliorated renal injury. Moreover, TLYS alleviated the mitophagy clearance deficiency. In conclusion, our study showed that TLYS decoction can ameliorate mitochondrial dynamics by reducing oxidative stress and regulating mitophagy, thereby relieving renal injury, protecting renal function, and reducing renal fibrosis. This study provides support for the application of and further research on TLYS decoction.